Honey Composition and Properties - Imran, Muhammad; Haseeb Ahmad, Muhammad; Shabir Ahmad, Rabia (IntechOpen, 2023)
Honey is a natural food product with health benefits due to its numerous functional components that help to prevent and cure various diseases. This book provides a comprehensive overview of honey and honey production. The chapters discuss beekeeping practices, the geographical, entomological, and botanical origin of honey, the characteristics and properties of honey, the therapeutic and medicinal potential of honey, and honey's utilization in processed food products.